2008
DOI: 10.1182/blood-2008-03-147017
|View full text |Cite
|
Sign up to set email alerts
|

ALK+ histiocytosis: a novel type of systemic histiocytic proliferative disorder of early infancy

Abstract: We report 3 cases of a previously uncharacterized form of histiocytosis presenting in early infancy and showing ALK immunoreactivity. The patients presented with pallor, massive hepatosplenomegaly, anemia, and thrombocytopenia. Liver biopsy showed infiltration of the sinusoids by large histiocytes with markedly folded nuclei, fine chromatin, small nucleoli, and voluminous lightly eosinophilic cytoplasm that sometimes was vacuolated or contained phagocytosed blood cells. One patient developed cutaneous infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 20 publications
(15 reference statements)
4
86
1
Order By: Relevance
“…Finally, Chan et al (2008) have described three cases of systemic histiocytosis, presenting in early infancy, expressing ALK or the TPM3-ALK chimeras. It is unclear whether these disorders are indeed true malignancies or due to an aberrant hyperproliferation of macrophages and dendritic cells, driven by the ectopic ALK expression.…”
Section: Alk Fusion Proteinsmentioning
confidence: 99%
“…Finally, Chan et al (2008) have described three cases of systemic histiocytosis, presenting in early infancy, expressing ALK or the TPM3-ALK chimeras. It is unclear whether these disorders are indeed true malignancies or due to an aberrant hyperproliferation of macrophages and dendritic cells, driven by the ectopic ALK expression.…”
Section: Alk Fusion Proteinsmentioning
confidence: 99%
“…11 Subsequently, ALK rearrangements were found in several phenotypically different hematologic neoplasms [12][13][14] and in histogenetically unrelated inflammatory myofibroblastic tumor. [15][16][17][18] Recently, ALK rearrangements and EML4-ALK and KIF5B-ALK fusions were discovered in a subset of non-small cell lung carcinomas; 19,20 proteomics reports suggested a possible TPM4-ALK fusion in esophageal carcinoma; 21,22 and an exon array profiling study demonstrated the EML4-ALK fusion in 2.5% of breast and colon cancers.…”
mentioning
confidence: 99%
“…20,21), and ALK-positive histiocytosis (TPM3; ref. 22) Besides, some ALK fusions have been reported without showing histopathologic evidence: TPM4-ALK in esophageal squamous cell carcinoma (23,24), TFG-ALK in lung adenocarcinoma (25), and EML4-ALK in colon and breast carcinomas (26). The wild-type ALK is mainly expressed in the developing nervous system, and is usually not expressed in other normal tissues (27).…”
Section: Introductionmentioning
confidence: 99%